Pemetaan Jasa Ekosistem Penyedia di Daerah Aliran Sungai Mamasa - Dara, Marleny; Aqwan, Chairil; Nasir, Anugrahandini; Nurul Mukhlisa, Andi (Pangale Journal of Forestry and Environment, 2025)
The Mamasa watershed is one of the important areas in the Mamasa–Saddang hydrological system, which has a strategic ecological function in providing ecosystem services. Changes in land cover, pressure on land use, and variations in geomorphological characteristics have the potential to affect the capacity to provide ecosystem services in the region. Therefore, a comprehensive understanding of the potential for ecosystem services is very important as a basis for sustainable development planning and the preparation of environmental carrying capacity studies within the framework of the Strategic Environmental Assessment (SEA). This study aims to describe and map the potential for ecosystem service provision in the Mamasa watershed, which covers the districts of Mamasa, Polewali Mandar, Pinrang, Tana Toraja, and Enrekang. The methods used include expert judgment for geomorphological and land cover assessment, which are then analyzed using a Pairwise Comparison Matrix and Geographic Information System. The results of the study show that the Mamasa watershed has 12 types of land cover and 8 types of geomorphology. In terms of food provision ecosystem services, the moderate category dominates at 53.77% and is mainly located in the upper reaches with an area of 25,463.67 ha. Clean water provision ecosystem services are also dominated by the moderate category at 56.18%, mainly distributed in the downstream area covering an area of 25,247.22 ha. For fiber provision ecosystem services, the moderate category dominates at 30.10% and covers the upstream area with an area of 24,649.19 ha. Meanwhile, biomass fuel ecosystem services show a dominance of the medium category at 30.10% with an area of 20,845.75 ha, which is also located in the upstream area. These findings provide a comprehensive spatial overview for sustainable natural resource management planning in the Mamasa watershed.